Genetic variants and phenotype analysis in a five-generation Chinese pedigree with PCDH19 female-limited epilepsy - Zhou, Wenjuan; Ouyang, Yuzhen; Ji, Yuqiao; Xi, Qiong; Zhao, Lingling (Frontiers in Neurology, 2023)
Objective Albeit the gene of PCDH19-FE was ascertained, the correlation of gene mutation, PCDH19 protein structure, and phenotype heterogeneity remained obscure. This study aimed to report a five-generation pedigree of seven female patients of PCDH19-FE and tried to explore whether two variants were correlated with PCDH19 protein structure and function alteration, and PCDH19-FE phenotype. Methods We analyzed the clinical data and genetic variants of a PCDH19-FE pedigree, to explore the phenotype heterogeneity of PCDH19-FE and underlying mechanisms. In addition to the clinical information of family members, next-generation sequencing was adopted to detect the variant sites of probands with validation by sanger sequencing. And the sanger sequencing was conducted in other patients in this pedigree. The biological conservation analysis and population polymorphism analysis of variants were also performed subsequently. The structure alteration of mutated PCDH19 protein was predicted by AlphaFold2. Results Based on a five-generation pedigree of PCDH19-FE, missense variants of c.695A>G and c.2760T>A in the PCDH19 gene were found in the heterozygous proband (V:1), which resulted in the change of amino acid 232 from Asn to Ser (p.Asn232Ser) and amino acid 920 from Asp to Glu (p.Asp920Glu) influencing PCDH19 function. The other six females in the pedigree (II:6, II:8, IV:3, IV:4, IV:5, IV:11) exhibited different clinical phenotypes but shared the same variant. Two males with the same variant have no clinical manifestations (III:3, III:10). The biological conservation analysis and population polymorphism analysis demonstrated the highly conservative characteristics of these two variants. AlphaFold2 predicted that the variant, p.Asp920Glu, led to the disappearance of the hydrogen bond between Asp at position 920 and His at position 919. Furthermore, the hydrogen bond between Asp920 and His919 also disappeared when the Asn amino acid mutated to Ser at position 232. Conclusion A strong genotype-phenotype heterogeneity was observed among female patients with the same genotype in our PCDH19-FE pedigree. And two missense variants, c.695A > G and c.2760T>A in the PCDH19 gene, have been identified in our pedigree. The c.2760T>A variant was a novel variant site probably related to the PCDH19-FE.